2009
DOI: 10.1016/j.otsr.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dysplasia of the hip: Is acetabular retroversion a crucial factor?

Abstract: Level IV, retrospective diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Isolated open or arthroscopic management with an aggressive anterior rim decompression may fail to address the overall deformity and result in iatrogenic anterior and posterior wall deficiency. An “anteverting” periacetabular osteotomy to provide anteversion correction of the acetabulum and improve mechanics between the femoral head-neck junction and the acetabular rim may be more appropriate in this setting [31] [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Isolated open or arthroscopic management with an aggressive anterior rim decompression may fail to address the overall deformity and result in iatrogenic anterior and posterior wall deficiency. An “anteverting” periacetabular osteotomy to provide anteversion correction of the acetabulum and improve mechanics between the femoral head-neck junction and the acetabular rim may be more appropriate in this setting [31] [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Although it generally is believed that anteversion of the acetabulum is associated with developmental dysplasia of the hip, there has been controversy regarding whether this actually is seen. Several studies have shown some dysplastic hips tend to be retroverted [4,14,15,19]. It remains unclear whether developmentally dysplastic hips should be discussed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Some quantitative radiographic indices for acetabular retroversion have been reported [7,9,19,24,30]. Nehme et al [19], focusing on the crossover point, observed the anterior wall crossing the posterior wall, and calculated a ratio of the distance between the acetabular lateral edge and the crossover point divided by the total length of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 7 The ARI is a quotient between the length of overlap of the anterior rim in comparison with the entire length of the lateral acetabular opening (Fig. 1d).…”
mentioning
confidence: 99%